Pulmonary Limited MPO-ANCA Microscopic Polyangiitis and Idiopathic Lung Fibrosis in a Patient with a Diagnosis of IgA Nephropathy - Alwin Tilanus; Patricia Van der Niepen; Caroline Geers; Karl Martin Wissing (Case Reports in Nephrology)
We present a case of a male patient with chronic renal insufficiency, due to crescentic glomerulonephritis with IgA deposits, who successively developed (idiopathic) thrombocytopenic purpura (ITP) and MPO-ANCA microscopic polyangiitis (MPA) with pulmonary fibrosis. The patient presented with cough, weight loss, and dyspnea on exertion. CT imaging and pulmonary function tests were compatible with interstitial pneumonitis with pulmonary fibrosis. Laboratory results showed high MPO-ANCA titers; the urinary sediment was bland. The patient was treated successfully with cyclophosphamide and methyl-prednisolone. This unique case illustrates the diagnostic and therapeutic challenges of an unusual presentation of microscopic polyangiitis presenting first as isolated kidney disease with recurrence in the form of pneumonitis without renal involvement, in association with renal IgA deposits and ITP as coexisting autoimmune conditions.